UBE2I stimulates female gonadal differentiation in chicken (Gallus gallus) embryos - Kai JIN; Jing ZHOU; Qi-sheng ZUO; Jian-cheng LI; SONG Jiuzhou; Ya-ni ZHANG; Guo-bing CHANG; Guo-hong CHEN; Bi-chun LI (Journal of Integrative Agriculture, 2021)
Without known analogous sex-determining factors like SRY (sex determining region Y) in mammals, the chicken (Gallus gallus) sex determination mechanism still remains unclear, which highly restricts the biological research on chicken development and poultry single-sex reproduction. Here we not only characterized a new female-biased gene UBE2I and identified the expression pattern by qRT-PCR, but also described the functional role of UBE2I in the gonadal development of chicken embryos. Results showed that UBE2I exhibited a female-biased expression pattern in the early stage of PGCs (primordial germ cells) in embryonic gonads and robust expression in ovaries of newborn chickens. Most importantly, we successfully developed an effective method to interfere or overexpress UBE2I in chicken embryos through the intravascular injection. The qRT-PCR analysis showed that the sex-related genes (FOXL2, CYP19A1 and HINTW) in females were upregulated (P<0.05) under the overexpression of UBE2I and the sex-related genes (SOX9, DMRT1 and WT1) in females were downregulated (P<0.05) after interfering UBE2I. Furthermore, the change of UBE2I expression was associated with the level of estradiol and its receptors (AR and ESR), which suggests that UBE2I is necessary to initiate the female-specific development in chickens. In conclusion, this work demonstrates that UBE2I is a crucial sex differentiation-related gene in the embryonic development of chickens, which provides insights for further understanding the mechanism of sex determination in chickens.